2021
DOI: 10.1093/braincomms/fcab252
|View full text |Cite
|
Sign up to set email alerts
|

AAV1.NT-3 gene therapy in a CMT2D model: phenotypic improvements in GarsP278KY/+ mice

Abstract: Glycyl tRNA synthetase (GARS) mutations are associated to the Charcot-Marie-Tooth type-2D. The GarsP278KY/+ model for Charcot-Marie-Tooth type-2D is known best for its early onset severe neuropathic phenotype with findings including reduced axon size, slow conduction velocities and abnormal neuromuscular junction. Muscle involvement remains largely unexamined. We tested the efficacy of neurotrophin 3 (NT-3) gene transfer therapy in two Gars mutants with severe (GarsP278KY/+) and milder (GarsΔETAQ/+) phenotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 69 publications
2
27
0
Order By: Relevance
“…We also assessed the status of NMJ in response to NT-3 gene therapy in this model as there is evidence that changes in endplate morphology and NMJ remodeling occur with aging and precede loss of fast motor units [ 20 ]. Using immunohistochemistry-based parameters [ 11 ], we analyzed a total of 330 NMJs derived from intrinsic foot muscles of NT-3 treated and untreated aged C57BL/6 mice. This analysis showed that AAV1.NT-3 gene therapy, at 6 months of treatment gave rise to a 29.7% increase of innervated NMJs ( p = 0.0123).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also assessed the status of NMJ in response to NT-3 gene therapy in this model as there is evidence that changes in endplate morphology and NMJ remodeling occur with aging and precede loss of fast motor units [ 20 ]. Using immunohistochemistry-based parameters [ 11 ], we analyzed a total of 330 NMJs derived from intrinsic foot muscles of NT-3 treated and untreated aged C57BL/6 mice. This analysis showed that AAV1.NT-3 gene therapy, at 6 months of treatment gave rise to a 29.7% increase of innervated NMJs ( p = 0.0123).…”
Section: Resultsmentioning
confidence: 99%
“…Lumbrical muscles collected from treated and untreated mice ( n = 4 for both cohorts with equal sex distribution) were processed as described previously [ 11 ]. Muscles were fixed and stained with primary antibodies (Acetylcholine receptor (AChR) antibody, α Bungarotoxin, T1175, 1:500; Anti Neurofilament 200 antibody, N4142, 1:500; SV2 antibody, AB_2315387, 1:50) [ 49 , 50 ], followed by incubation with secondary antibodies (Alexa Fluor 488 conjugated anti-rabbit and anti-mouse IgG, 1:500).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mature neurotrophins then bind to their corresponding receptors, the Trk family of receptor tyrosine kinases, and regulate neuronal survival and synaptic plasticity [100,101]. Aberrant expressions of NT-3 and NT-4/5 participate in pathophysiological conditions including motor dysfunction, cognitive decline, stroke, and SCZ [102][103][104][105][106][107].…”
Section: Other Neurotrophinsmentioning
confidence: 99%
“…It also increased both myelin thickness and muscle fiber size and improved the denervated state of NMJ. On the basis of the multiple effects of this molecule, a potential benefit could be predicted in patients with mutations in GARS1 and other aminoacyl tRNA synthetases [55 ▪▪ ]. Zuko et al found that mutant glycyl-tRNA synthetases cause an impairment in mRNA translation elongation and that transgenic tRNA Gly overexpression rescues protein synthesis and peripheral neuropathy in mice and fly models of GARS1-CMT/CMT2D.…”
Section: Treatmentmentioning
confidence: 99%